ANALYSIS OF LIQUIDITY AND PROFITABILITY FOR MEASURE FINANCIAL PERFORMANCE IN COAL MINING SERVICES INDUSTRIES LISTED ON IDX - Adibah, Faroh (Jurnal Ilmiah Mahasiswa FEB, 2012)
The objective of this study is to analyze of liquidity and profitability for measure financial performance in Coal Mining Services Industries Listed on IDX. This journal uses the financial performance framework and public data from 10 companies listed in Indonesian Stock Exchange along the year 2007-2011. This study uses the ratio of external comparisons include comparisons with other similar or industry average at the same point and also standard ratio in every kind of financial ratios. The results show that all variables may be expressed normally distributed. There is no difference in the financial performance of coal mining services industries are calculated using the ratio of liquidity and ratio of profitability. The financial performance of coal mining services company that is best for variable CR mean, QR mean, ROI mean and ROA mean is the variable of CR mean evidenced by obtaining the greatest results from coal services than other variables. The results help the company maintain and improve financial situation. Keywords: liquidity, profitability and performance